The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11274-021-03099-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activity of Evernia prunastri extracts and their isolates

Abstract: Lichens are symbiotic organisms formed by a fungus and one or more photosynthetic partners which are usually alga or cyanobacterium. Their diverse and scarcely studied metabolites facilitate adaptability to extreme living conditions. We investigated Evernia prunastri (L.) Ach., a widely distributed lichen, for its antimicrobial and antioxidant potential. E. prunastri was sequentially extracted by hexane (Hex), dichloromethane (DCM) and acetonitrile (ACN) that were screened for their antioxidant and antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…So far over 70 different metabolites have been identified and characterized in E. prunastri, and evernic acid is regarded as one of its major secondary metabolites [42]. In our study, evernic acid was cytotoxic to the A-172 cell line in a broad range of concentrations (10-100 µM); however, the cytotoxic effect was moderate -the viability dropped to ~80%, as compared to the vehicle-treated control.…”
Section: Discussionmentioning
confidence: 53%
“…So far over 70 different metabolites have been identified and characterized in E. prunastri, and evernic acid is regarded as one of its major secondary metabolites [42]. In our study, evernic acid was cytotoxic to the A-172 cell line in a broad range of concentrations (10-100 µM); however, the cytotoxic effect was moderate -the viability dropped to ~80%, as compared to the vehicle-treated control.…”
Section: Discussionmentioning
confidence: 53%
“…Another possible mechanism of UA activity against S. aureus is binding to allosteric sites on the protein surface of FabI (enoyl reductase enzyme), which affects enzyme activity [ 48 ]. Usnic acid was found to be active against S. aureus , with a MIC of 21 μg/ml [ 50 ]. Minimum inhibitory concentration values of UA against different clinical isolates of S. aureus range from 8 to 50 μg/ml [ 33 , 34 , 43 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evernic acid acts as an antimicrobial agent, inhibiting the growth of Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , and Candida albicans (MIC values from 0.98 to 125 µg/mL) [ 84 ]. In deepening the mechanism of these effects, it was observed that the virulence of the Gram-negative opportunistic pathogen Pseudomonas aeruginosa was reduced by inhibiting quorum sensing on diverse Pseudomonas aeruginosa strains (54% of gfp expression of lasB-gfp and 50% of rhlA-gfp at a concentration of 116 µM).…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…It should be also noted that evernic acid is a moderate inhibitor of tumor promoter-induced Epstein–Barr virus activation (64.6% of an inhibitory effect at a concentration of 50 µM) [ 71 ]. Finally, regarding the toxicity of this compound, in silico prediction tests showed no mutagenic effects, no tumorigenic effects, no reproductive alterations, and no irritant effects [ 84 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%